Effect of intercropping sweet potato (Ipomea batatas) with pigeonpea (Cajanus cajan) and okra (Hibiscus esculentus) on economic yield of maize (Zea mays) and maximization of land use - EMHU, F N; AGBOOLA, A A (The Indian Journal of Agricultural Sciences, 2013)
A study was carried out during 1991-92 to determine the response of maize (Zea mays L.) in association withsweet potato (Ipomea balatas (L.) Lam), pigeonpea (CaJanus cajan (L.) Millsp.) and okra (Hibiscus esclentus L.) onmaximization ofland-use as well as the economic Â·yield and productivity in the mixtures. Maize tasselled earlier in themixtures than in the sole crop though not significant, economic yields were significantly higher in sole crops than inmixtures. Land-equivalent ratio were higher in the various mixtures than in the sole crops. The combination of maize.okra, sweet potato and pigeonpea gave the highest land-equivalent ratio of 1.93.